Modeling the Survival of Escherichia coli O157:H7 Under Hydrostatic Pressure, Process Temperature, Time and Allyl Isothiocyanate Stresses in Ground Chicken Meat - Huang, Chi-Yun; Sheen, Shiowshuh; Sommers, Christopher; Sheen, Lee-Yan (Frontiers in Microbiology, 2018)
Shiga toxin-producing Escherichia coli O157:H7 (STEC) is a common contaminant in meat and poultry. We investigated the use of non-thermal High Pressure Processing (HPP), with or without allyl isothiocyanate (AITC) essential oil, to kill STEC in ground chicken meat. Temperature was found an important factor affecting the inactivation of STEC in addition to pressure and process time. A full factorial experiment design (4 factors x 2 levels) was used to facilitate and evaluate the effect of pressure (250-350MPa), operation temperature (-15 - 4°C), AITC concentration (0.05-0.15%, w/w), and pressure-holding time (10-20 min) on the inactivation of STEC. A linear model (a polynomial equation) was developed to predict/describe those four parameters’ impact on E. coli O157:H7 survival (R2 = 0.90), as well as a dimensionless nonlinear model. Both types of models were validated with data obtained from separate experimental points. The dimensionless model also demonstrated that it may predict the lethality (defined as the log CFU/g reduction of STEC before and after treatment) reasonably well with some factors set slightly outside the design ranges (e.g. a wider application than the linear model). The results provide important information regarding STEC survival as affected by HPP (e.g. pressure, time and temperature) and AITC. With the addition of AITC, the hydrostatic pressure may be lowered to the 250-350 MPa level. Regulatory agencies and food industry may use those models for STEC risk assessment in ground chicken meat. A storage test (at 4 and 10°C, 10 days) after HPP+AITC treatment indicated that AITC may continue depressing or killing the pressure-damaged cells.